Hyponatremia and Cognitive Impairment in Patients Treated with Peritoneal Dialysis - Xu, Rong (Clin J Am Soc Nephrol, 2015)
BACKGROUND AND OBJECTIVES: Hyponatremia has been identified as a relevant factor for cognitive impairment but has not been investigated in patients receiving peritoneal dialysis (PD). This study investigated the relationship between hyponatremia and cognitive functions in PD patients. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: A total of 476 clinically stable patients from five PD units who were older than 18 years of age and had undergone PD for at least 3 months between March 2013 and March 2014 were enrolled in this multicenter cross-sectional study. Global cognitive function was measured using the Modified Mini-Mental State Examination (3MS); executive function, by trail making tests A (trails A) and B (trails B); and immediate memory, delayed memory, and language ability, by subtests of Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). Hyponatremia was defined as serum sodium level ≤135 mmol/L, which was calculated as the mean of measurements taken over the preceding 3 months. RESULTS: Fifty patients (10.5%) had hyponatremia; these patients tended to be older and less educated, to have less inflammation, and to have the higher prevalence of cognitive impairment. They also had lower scores on RBANS subtests. After adjustment for demographic and clinical confounders, hyponatremia was independently associated with lower 3MS score (coefficient, −5.28; 95% confidence interval [CI], −8.44 to –2.13) and longer completion time of trials A (coefficient, 22.68; 95% CI, 3.44 to 41.92) and B (coefficient, 45.56; 95% CI, 1.30 to 89.81). After additional adjustment for laboratory measures, hyponatremia was still associated with 3MS score and completion time of trails A. Hyponatremia was independently associated with CI (odds ratio, 2.17; 95% CI, 1.02 to 4.94) and executive dysfunction (odds ratio, 2.43; 95% CI, 1.01 to 5.87) using multivariate logistic regression analysis. Sensitivity analyses with multivariable models that included propensity score still supported the association between hyponatremia and cognitive impairment. CONCLUSIONS: Hyponatremia was associated with global and specific cognitive impairment in PD patients.